Mothers' Awareness Regarding Home Care Management of a Preterm Baby at the Rapareen Pediatric Teaching Hospital in Erbil City - Chawarwan Saleem Abdullah; Shukir Saleem Hassan (Hawler Medical University, 2019)
Background and objectives: Preterm birth is a global health issue that occurs in every country. Every year, 15 million preterm infants are born worldwide, and one out of ten is a preterm infant. Sixty percent of preterm infants are born in developing countries. This study aimed to assess mothers' awareness regarding home care management of a preterm baby at the Rapareen Pediatric Teaching Hospital in Erbil in the Kurdistan Region of Iraq. Method: A quantitative, descriptive, cross-sectional study was carried out in the Neonatal Intensive Care Unit at the Rapareen Pediatric Teaching Hospital in Erbil from the 7th of Oc-tober 2018 to the 15th of October 2019. A purposive, non-probability sampling technique was used, and 130 mothers were respectively recruited to the study. A questionnaire was developed by the researcher and the research data were collected by direct, face-to-face interviews. Descriptive statistics in the form of frequencies, percentages, and interferential chi-square test were used to analyze the data. Results: More than half (53.8%) of the mothers were 25-33 years old and the majority (77.7%) of them were housewives. The main finding of the study is that most mothers had a neutral level of awareness regarding thermoregulation, breastfeeding, vaccinations, and recognizing danger signs. At the same time, most of the mothers were not aware of the infection prevention, and there was a very high, statistically significant association between mothers' awareness regarding thermoregulation and occupation and a type of family. Furthermore, there was a statistically significant association between the mothers' awareness regarding breastfeeding and their residency and a type of delivery, and a statistically significant association between the mothers' awareness regarding infection prevention and their occupation and economic status. Finally, there was a statistically significant association between the mothers' awareness of vaccinations and their age and the type of delivery...